Hollywood Leadership Theory, Part 2: Examples from World Leaders - Christopher Barrick (Academic Chairpersons Conference Proceedings, 2023)
Following the success of last year’s presentation at the 39th Academic Chairpersons Conference, Part 2 of the Hollywood Leadership Theory continues to demonstrate how leadership advice can be found in television and movies as readily as it is in journals and books.
Keywords: leadership; movies; leader; president; world; national; headship; Hollywood; television